Analysis of Language Errors in Student Institutional Administration (BEM) FKIP UNRI - Ifebri Ifebri; Hermandra Hermandra; Charlina Charlina (Journal of Education Technology Information Social Sciences and Health, 2024)
The aim of this research is to identify and describe forms of language errors (syntax) in the field of phrases and sentences in the FKIP UNRI student institutional administration (BEM) uploaded to the institutional Instagram account. Researchers used descriptive qualitative research methods. Data collection techniques include documentation techniques, reading techniques and note-taking techniques. The results of this research found 99 data on syntactic errors, 72 of which were phrase errors and 27 were sentence errors. Researchers concluded that the most errors occurred in excessive use of elements, namely 34 data errors. Meanwhile, the fewest errors were 2 data errors each on the influence of regional languages, reciprocal use, and non-parallel compound sentences.